2014
DOI: 10.1167/14.3.25
|View full text |Cite
|
Sign up to set email alerts
|

The perception of three-dimensional cast-shadow structure is dependent on visual awareness

Abstract: In the present study we examined whether the perception of depth from cast shadows is dependent on visual awareness using continuous flash suppression (CFS). As a direct measure of how the visual system infers depth from cast shadows, we examined the cast-shadow motion illusion originally reported by Kersten, Knill, Mamassian, and Bulthoff (1996), in which a moving cast shadow induces illusory motion in depth in a physically stationary object. In Experiment 1, we used a disparity defined probe to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Despite the strength of this phenomenon, the underlying neuronal mechanisms are unknown. A recent study has revealed that the motion in depth in the SOC illusion is perceptually comparable with that represented by binocular disparity [24]. Taken together with the observations previously described, this finding strongly suggests that the hMT+ is also involved in the perceptual process of the SOC illusion.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Despite the strength of this phenomenon, the underlying neuronal mechanisms are unknown. A recent study has revealed that the motion in depth in the SOC illusion is perceptually comparable with that represented by binocular disparity [24]. Taken together with the observations previously described, this finding strongly suggests that the hMT+ is also involved in the perceptual process of the SOC illusion.…”
Section: Introductionsupporting
confidence: 75%
“…The direct inputs to the hMT+ from subcortical structures on the visual pathway, such as the lateral geniculate nucleus (LGN), superior colliculus (SC), and pulvinar (PL), have been considered the most likely alternative pathway, bypassing V1 and thereby accounting for the residual vision of blindsight patients [42, 43]. It has also been shown that the motion of the square in depth in the SOC illusion can be perceived even when the motion of the cast shadow is masked and processed unconsciously [24]. These observations suggest that there may be different visual pathways for processing monocular depth cues with and without consciousness, and that the hMT+ may be a key area for integrated motion perception in depth produced by those cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be related to the evidence that the shadow of a person's body contributes to the connection between personal and extrapersonal space and triggers an automatic focus of attention toward the body part casting the shadow (Pavani & Galfano, 2015). Khuu, Gordon, Balcomb and Kim (2014) present results indicating that visual awareness is necessary for the perception of illusory motion from changes in cast shadows. The authors suggest that the perception of cast shadows is guided by two processes, one implicit that is responsible for the recognition of objects, and another demanding visual awareness to infer the object's 3D location.…”
Section: Introductionsupporting
confidence: 62%
“…Note that such motion types are examples of motion informing the global form of the stimulus. This process might very well involve inputs from the ventral form pathway [47] , which might be reliant on conscious awareness for recognition [22] . Accordingly, such ‘motion forms and shapes’ might be susceptible to binocular suppression, indicating a dependency on visual awareness.…”
Section: Discussionmentioning
confidence: 99%